Association Between Kinematic Center and Anatomy, The Function of Temporomandibular Joint - Zahid Sarfaraz Khan, Syeda Gulrukh Saba Shah, Ambereen Humayun, Zakir Ullah Khan, Waqas Ali, Maira Iqbal, Nabiha Naeem, Arshad Farid, Irfan Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Evident from the literature, the kinematic center (KC) has been proposed as a reference point for representing movements of the TMJ, which includes jaw openings, closings, and protrusions and retrusions. Objective: The purpose of this study was to determine whether the KC lies in a peculiar anatomical point and whether its trajectory reflects intra-articular distances. Methods: Dynamic stereo-metry was used to track Four closings and openings and Four protrusions/retrusion in fourteen asymptomatic individuals (8 females and 6 males, ages 21-40). Results: According to a 3D lattice (0.5 mm grid) constructed solidly around each condyle, the KC had the largest cross-correlation between protrusion-retrusion paths and opening-closing paths. On closing, KC trajectories were more cranial than on opening, consistent with smaller intraarticular distances on closing. Yet KCs never fell on main condylar axes (distance, 4.5 mm) or coincided with points approximating fossa shapes (distance, 12.5 mm). Conclusion: In this regard, it is unclear what the significance of the kinematic center is anatomically and functionally.